A Two-stage Stochastic Model for Coordinated Operation of Natural Gas and Microgrid Networks - Zandrazavi, Seyed Farhad [UNESP]; Tabares, Alejandra; Franco, John Fredy [UNESP]; Shafie-Khah, Miadreza; Soares, Joao; Vale, Zita (Institute of Electrical and Electronics Engineers (IEEE), 2023)
On the one hand, natural gas-fired dispatchable distributed generation (DG) units and batteries can be used in microgrids (MG) to cope with the intermittency of renewable energy resources such as wind turbines and photovoltaic units. On the other hand, the uncertainties in MG influence the gas system through the gas-fired DG units, making these systems' optimal operation interdependent. As a result, firstly, a novel mixed-integer nonlinear model for optimal integrated operation of gas and MG networks is proposed. Then, the model is linearized, guaranteeing the optimality of solutions and enhancing the model's tractability. Finally, a two-stage stochastic mode is proposed to include the uncertainties linked to electricity price, wind power speed, solar irradiation, and demand. In contrast, the value of the stochastic solution measurement is calculated to justify the use of the stochastic approach. The results indicate that the total cost of the integrated system decreased by 17.82% using the stochastic model compared to the deterministic approach.
Keywords: energy management; gas distribution network; microgrid; renewable energy; stochastic programming